Transcriptome and Gut Microbiota Profiling Revealed the Protective Effect of Tibetan Tea on Ulcerative Colitis in Mice - Wang, Ning; Wu, Tao; Du, Di; Mei, Jie; Luo, Huibo; Liu, Zishan; Saleemi, Muhammad Kashif; Zhang, Runhui; Chang, Candace; Mehmood, Muhammad Aamer; Zhu, Hui (Frontiers in Microbiology, 2022)
Traditionally, Ya'an Tibetan tea is routinely consumed by local people in Tibet region. It is believed to possess promising anti-inflammatory benefits. This study was conducted to elucidate the protective impact of Tibetan tea extract (TTE) on dextran sodium sulfate (DSS)-induced colitis in mice. The mice were split into four groups namely control group (C), Tibetan tea group (T), DSS-induced model group (CD), and Tibetan tea + DSS group (TD). The intake of TTE significantly reduced the clinical symptoms UC by alleviating the impact of cellular damage, reducing glandular hypertrophy, and the infiltration of inflammatory cells. UC led to a prominent shift of the microbial communities in the gut. Interestingly, the beneficial microbes, such as Lactobacillus reuteri, Bifidobacterium choerinum and Lactobacillus intestinalis were significantly increased in the TTE-treated mice, when compared to the any other experimental group. The transcriptome analysis revealed that positive effect of TTE on UC could be attributed to the changes in G alpha (i) signaling pathway and innate immune system. The genes related to inflammation and immune system pathways were differentially expressed in the TTE treated group. Moreover, the relative expression of genes linked to inflammatory TLR4/MyD88/NF-κB signaling pathway was significantly downregulated towards the level of normal control samples in TD group. Overall, this study revealed the modulatory effect by which TTE reversed the development and severity of chronic colon damage.